2010
DOI: 10.1186/1472-6947-10-54
|View full text |Cite
|
Sign up to set email alerts
|

A targeted decision aid for the elderly to decide whether to undergo colorectal cancer screening: development and results of an uncontrolled trial

Abstract: BackgroundCompeting causes of mortality in the elderly decrease the potential net benefit from colorectal cancer screening and increase the likelihood of potential harms. Individualized decision making has been recommended, so that the elderly can decide whether or not to undergo colorectal cancer (CRC) screening. The objective is to develop and test a decision aid designed to promote individualized colorectal cancer screening decision making for adults age 75 and over.MethodsWe used formative research and cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 33 publications
0
60
0
Order By: Relevance
“…Two of the trials focused on older adults, with one focusing on adults aged ≥65 years 50 and the other on adults aged ≥75 years. 40 Three of the trials focused on specific populations, including individuals with low education, 47 individuals with low SES, 41 and Hispanic or Latino individuals with limited English proficiency. 51 …”
Section: Evidence Synthesismentioning
confidence: 99%
“…Two of the trials focused on older adults, with one focusing on adults aged ≥65 years 50 and the other on adults aged ≥75 years. 40 Three of the trials focused on specific populations, including individuals with low education, 47 individuals with low SES, 41 and Hispanic or Latino individuals with limited English proficiency. 51 …”
Section: Evidence Synthesismentioning
confidence: 99%
“…A systematic review of decisional role preferences among cancer patients has shown an increasing trend of patients being interested in more participation during TDM (Tariman, Berry, Cochrane, Doorenbos, & Schepp, 2010). In order to meet and facilitate the patient’s preferred level of participation during TDM, interventional studies geared toward increasing a patient’s decisional satisfaction, reducing decisional conflict, and preventing anxiety and depression related to TDM have been steadily increasing in numbers (Allen et al, 2010; Caldon et al, 2010; Evans et al, 2010) with some studies targeting the elderly cancer patient population (Lewis et al, 2010; van Tol-Geerdink et al, 2008). …”
mentioning
confidence: 99%
“…The values clarification exercise was adapted from one developed for use in colorectal cancer screening among elderly people33 to capture the main issues involved in the decision, including features identified as important to patients with colorectal cancer9 (see online supplementary table S1). Patients were asked to complete the questionnaire on the computer, selecting 1 of the 2 options presented for all 10 questions.…”
Section: Methodsmentioning
confidence: 99%